Growth performance of the green tiger prawn Penaeus semisulcatus De Haan in cages in the Gulf of Mannar off Mandapam, Southeast Coast of India - Maheswarudu, G. (2019)
Two experiments were conducted in rectangular box type cages. In experiment 1, growth of juveniles was compared at two densities (13 ind.mˉ² and 21 ind.mˉ²) with the clam meat. In experiment 2, growth of juveniles was studied at a single density (13 ind.mˉ²) but with two different feeds (squid and compound pellet diet). In experiment 1, growth of both male and female significantly differed between the two densities, being higher at the lower density. In experiment 2, average growth performance of both male and female was higher with the compound diet. All males in the four treatments attained maturity at the age of 5 months. All females at the lower density reached maturity at the age of 6 months; this finding illustrates the suitability of low density culture for the development of broodstock in cages in the sea. Growth parameters (L∞ and k) were estimated for each sex in each treatment. As growth significantly differed between treatments for both sexes in the two experiments, L∞ and k differed accordingly, revealing the possibility of an influence of density and diet on the growth parameters. In all four treatments for both sexes, lifespan for Penaeus semisulcatus is estimated to 3+ years. The results of this study revealed that growth parameters such as L∞ and k are subject to variation depending on density and diet of the species in question.